2019
DOI: 10.2500/aap.2019.40.4267
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary and acquired angioedema

Abstract: Hereditary angioedema (HAE) is an autosomal dominant disorder defined by a deficiency of functional C1 esterase inhibitor (C1-INH). Acquired angioedema is due to either consumption (type 1) or inactivation (type 2) of CI-INH. Both HAE and acquired angioedema can be life-threatening. Of the three types of HAE, type 1 is most common, occurring in approximately 85% of patients and characterized by decreased production of C1-INH, which results in reduced functional activity to 5‐40% of normal. Type 2 occurs in 15… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
58
1
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 4 publications
0
58
1
5
Order By: Relevance
“…These include mutations in angiopoietin 1 gene (HAE‐ANGPT1), plasminogen gene (HAE‐PLG), and Kininogen‐1 gene 8,22–25 . Acquired angioedema (AAE‐C1‐INH) has mostly been reported in association with drugs, autoimmune diseases, and B‐cell lymphoproliferative disorders 26 . Patients with AAE have older age at onset (4th or 5th decades of life).…”
Section: Discussionmentioning
confidence: 99%
“…These include mutations in angiopoietin 1 gene (HAE‐ANGPT1), plasminogen gene (HAE‐PLG), and Kininogen‐1 gene 8,22–25 . Acquired angioedema (AAE‐C1‐INH) has mostly been reported in association with drugs, autoimmune diseases, and B‐cell lymphoproliferative disorders 26 . Patients with AAE have older age at onset (4th or 5th decades of life).…”
Section: Discussionmentioning
confidence: 99%
“…The primary differential diagnosis to be excluded is AAE, which can be secondary to hematologic malignancy (9). Patients who present at an advanced age need to be investigated to rule out AAE (9,10). The presence of B-symptoms, clinical examination, peripheral blood morphology, and immunoglobulin levels may be useful on a case to case basis (10).…”
Section: Discussionmentioning
confidence: 99%
“…This was timely recognized by several groups of investigators early during the pandemic (Roche & Roche, 2020; van de Veerdonk et al, 2020) and most recently was confirmed by a preliminary gene expression analysis study focusing on detailed evaluation of the RAS members, bradykinin and associated systems in samples from COVID‐19 and control patients (Garvin et al, 2020). This is a critical development, because bradykinin is a potent inflammatory mediator that has been associated with a number of pathophysiological conditions including angioedema (Patel & Pongracic, 2019), vasculitis (Karpman & Kahn, 2009), asthma (Ricciardolo et al, 2018), autoimmunity (Dutra, 2017), acute brain injury and neuroinflammation (Albert‐Weissenberger et al, 2013).…”
Section: Introductionmentioning
confidence: 99%